Compensatory Consumption and Urban Coffee Culture in Indonesia: A Qualitative Exploration of Emotional, Social, and Identity Motives - Mokhamad Eldon; Gautama Sastra Waskita (Kreatif Publisher, 2025)
This study examines the growing phenomenon of compensatory consumption within Indonesia’s rapidly expanding urban coffee culture, where consumers increasingly use café experiences to cope with emotional pressures, social expectations, and identity negotiations in modern city life. The research aims to explore the emotional, social, and symbolic motives driving coffee shop visits and how these motives shape consumption behaviors. Using a qualitative exploratory design, data were collected through in-depth interviews and participant observation across several urban specialty coffee shops in Indonesia. The findings reveal that consumers use coffee consumption as a mechanism for stress relief, social bonding, self-expression, and identity construction, positioning cafés as symbolic spaces that offer psychological compensation beyond functional product value. The study contributes to the existing literature by extending compensatory consumption theory to a Southeast Asian context and offers practical implications for coffee entrepreneurs in designing emotionally resonant and identity-centered customer experiences.